Solutions for enhancement of energy and exergy efficiencies in air handling units. (1st June 2020) - Liu, Wanli; Kalbasi, Rasool; Afrand, Masoud
Abstract: In this study, five layouts of using air-to-air heat exchangers (AAHE) were added in the Air Handling Unit (AHU) to diminish the cooling and heating coils energy usage through the energetic and exergetic analysis approach. In the first, second, and third techniques, the main focus is on cooling coil energy usage reduction. In the fourth and fifth layouts, new designs of using two AAHEs (i.e., primary and secondary units) have been incorporated to diminish simultaneously the energy demand of coils. The results showed if the objective function is defined to have the least cooling coil power, the fourth layout, and if the objective function is the lowest heating coil load, the fifth layout is recommended. In all layouts, installation of the AAHE reduced the irreversibility. In the best layout, AHU energy demand diminished by 23.68% which consequently improved the first law efficiency by 31.29%. Similarly, total exergy losses reduced by 26.58% and the second law efficiency improved by 11.79%. Calculations on cost analysis revealed that the least payback time and highest cost saving referred to first and fourth layouts, respectively. Highlights: Evaluating five layouts using heat recovery units to reduce AHU energy consumption. Layouts using two air-to-air heat exchangers have priority over other layouts. Power consumption and irreversibility decreased up to 23.7 and 26.6%, respectively. Least payback time and highest cost saving referred to first and fourth layouts.